Transcriptomic profiles of age-related genes in female trachea and bronchus - Liu, Jia; Lu, Haiyan; Hu, Silu; Wang, Faping; Tang, Xiaoju; Wan, Huajing; Luo, Fengming (Frontiers in Genetics, 2023)
Background: Studies demonstrated that age-related cellular and functional changes of airway significantly contribute to the pathogenesis of many airway diseases. However, our understanding on the age-related molecular alterations of human airway remains inadequate. Methods: Airway (trachea and bronchus) brushing specimens were collected from 14 healthy, female non-smokers with ages ranging from 20 to 60 years. Bulk RNA sequencing was performed on all the specimens (n = 28). Airway cell types and their relative proportions were estimated using CIBERSORTx. The cell type proportions were compared between the younger (age 20–40) and elder group (age 40–60) in the trachea and bronchus respectively. The linear association between cell type proportion and age was assessed using the Pearson correlation coefficient. Differentially expressed genes (DEGs) between the two age groups were identified using DESeq2. Three kinds of enrichment analysis of the age-related DEGs were performed, including Gene ontology (GO) enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, and disease enrichment analysis. Results: Sixteen and thirteen cell types were separately identified in tracheal and bronchial brushings, with the airway epithelial cells (including suprabasal, submucosal gland (SMG) goblet, serous, secretory, multiciliated, cycling.basal, basal cells) accounting for 85.1% in the trachea and 92.5% in the bronchus. The lymphatic cell and NK cells had a higher abundance ratio in the trachea, compared with the bronchus. The proportion of basal cells was negatively related to age both in the trachea and bronchus. Thirty-one and fifty-two age-related DEGs (p < 0.1) were identified in the trachea and bronchus, respectively. Among them, five common DEGs (CXCL2, CXCL8, TCIM, P4HA3, AQP10) were identified. Pathway enrichment analysis showed both tracheal and bronchial age-related DEGs were primarily involved in immune regulatory signaling pathways (TNF, NF-kappa B, IL-17 et al.). Disease enrichment analysis suggested that tracheal age-related DEGs significantly related to asthmatic pulmonary eosinophilia, and chronic airflow obstruction et al., and that bronchial age-related DEGs were enriched in airflow obstruction, bronchiectasis, pulmonary emphysema, and low respiratory tract infection et al. Conclusion: We found the proportion of basal cells decreased with age in both the trachea and bronchus, suggesting a weakening of their self-renew ability with age. We identified transcriptomic signature genes associated with the early aging process of the human trachea and bronchus, and provided evidence to support that changes in their immune regulatory function may play critical roles in age-related airway diseases.